Corporate boards and performance pricing in private debt contracts - Abu Bakar, Intan Suryani; Khan, Arifur; Mather, Paul R.; Tanewski, George A. (Elsevier B.V., 2018)
This paper investigates the effects of corporate governance on the use of performance pricing in debt contracts on a sample of newly syndicated loans in the U.S. private debt market. While cross-sectional results provide no evidence for the predicted relation between corporate governance quality and the likelihood of using performance pricing in debt contracts, there is evidence for the predicted positive relation between corporate governance quality and the use of interest-increasing performance pricing provisions. Evidence also provides support for the predicted negative relation between corporate governance quality and the use of financial ratio as the measure of performance underlying the provisions. Overall, empirical evidence supports the hypothesis that debt-holders perceive aspects of corporate governance to be beneficial and factor them in their contracting decisions.